Unlocking the Potential: Exploring Digital Social Marketing Technology in the Realm of Islamic Business Ethics - Darmawati, Darmawati; Ridha', Muhammad Afif; Afifah, Rahmah; bin Jadid, Bader Fahad Abdullah (JURNAL INDO-ISLAMIKA, 2023)
Digitalization has rapidly permeated various fields in today's era, with marketing being a prominent recipient of its transformative effects. The business landscape has witnessed a pronounced inclination towards ventures that are grounded in digital marketing. It captures the interest of diverse market segments, including both business entities and the general public. This research endeavors to examine the alignment of digital marketing practices with Islamic business ethics. Employing a qualitative research methodology with a descriptive analytical approach, this study gathered the data through a comprehensive review of relevant documentation. The study focuses on digital social marketing technologies employed on social media platforms and marketplaces as primary samples. Findings reveal that the application of digital marketing in the Indonesian context falls short of complete compliance with Sharia principles. Despite this, certain marketing processes do exhibit adherence to aspects of Islamic business ethics. Notably, emphasis within this context tends to be more pronounced in elements related to products and promotional media.